PENGARUH DISIPLIN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT. KERETA API INDOENSIA (PERSERO) DAERAH OPERASI 1 JAKARTA - Mutiara, Selvy; Agung, Syahrum; Suryana, Undang (INOVATOR, 2016)
The title of this research is "The Influence of Employees work discipline and stress". This research purpose is to know how far the Influences can influence the employee work discipline and stress in PT.KAI (persero) DAOP 1 Jakarta.The object of this research is PT.KAI (persero) DAOP 1 Jakarta. This research primary uses work descipline and stress as an independent variable and the the employees work as a dependent variable. The purpose of this research is to test and analyze the influence of work discipline and stress of employees. This research concern n 133 employees of PT. KAI (persero) DAOP 1 Jakarta. The data used in this research analyze into several measurement. The measurement are the validity, reliability, the correlation, regression, determination coefficient, and hypothesis in SPSS 18.0 application.The result of data analysis using SPSS 18.0 show there is no significant influence between worm discipline and stress of PT.KAI (persero) DAOP 1 Jakarta. The result show 0,184 interval (0,00-0,199). Based on the result, the relation between work discipline variable (X1) and work stress (X2) to employees work (Y) is very low. Whereas, the r point is 0,016 (1,6 %). So, if there is an analysis all the time using F test, F 1,920 < F table 3,08. Ho is accepted ( Ha is rejected). The conclusion of this research, there is no significant influence between work disciplime and work stress of employees work in PT. KAI (persero) DAOP 1 Jakarta.